Pd/CeO2−x Nanorod Catalysts for CO Oxidation: Insights into the Origin of Their Regenerative Ability at Room Temperature. Issue 10 (21st August 2014) - Zhou, Yunyun; Lawrence, Neil J.; Wu, Tai‐Sing; Liu, Jing; Kent, Patrick; Soo, Yun‐Liang; Cheung, Chin Li
Abstract The decrease in the activity of a catalyst after use is a persistent challenge in the chemical industry. We report that palladium‐decorated ceria (Pd/CeO2−x, in which 0≤x<0.5) nanorod catalysts demonstrate regenerative ability for carbon monoxide oxidation at room temperature. Pd/CeO2−x catalysts with 75 % decreased catalytic activity can be regenerated and restored almost 100 % of their original catalytic activity by exposing them to ambient conditions for 24 h. X‐ray spectroscopy studies of the atomic structures and oxidation states of palladium in the catalyst found that the formation of disordered palladium oxide is partly accountable for its observed regenerative catalytic property.